2021
DOI: 10.1002/cbf.3637
|View full text |Cite
|
Sign up to set email alerts
|

Gluconeogenesis is reduced from alanine, lactate and pyruvate, but maintained from glycerol, in liver perfusion of rats with early and late sepsis

Abstract: Sepsis induces several metabolic abnormalities, including hypoglycaemia in the most advanced stage of the disease, a risk factor for complications and death. Although hypoglycaemia can be caused by inhibition of hepatic gluconeogenesis, decreased and increased gluconeogenesis were reported in sepsis. Furthermore, gluconeogenesis from glycerol was not yet evaluated in this disease. The main purpose of this study was to investigate the gluconeogenesis from alanine, lactate, pyruvate and glycerol in rats with ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…In particular, it is converted to pyruvate via the gluconeogenesis pathway, and pyruvate can also be converted to alanine. 46 Alanine is both a nitrogen (N) donor and a nitrogen (N) acceptor obtained via transamination of pyruvate with various amino acids. 47 Several studies have demonstrated that serum levels of alanine metabolism in DVT patients and rats are inconsistent and that changes in alanine levels are closely related to its participation in multiple metabolic pathways, [37][38][39]43 including gluconeogenesis, bile acid synthesis, fatty acid synthesis, and amino acid metabolism.…”
Section: Metabolomic Characterization Of Dvtmentioning
confidence: 99%
“…In particular, it is converted to pyruvate via the gluconeogenesis pathway, and pyruvate can also be converted to alanine. 46 Alanine is both a nitrogen (N) donor and a nitrogen (N) acceptor obtained via transamination of pyruvate with various amino acids. 47 Several studies have demonstrated that serum levels of alanine metabolism in DVT patients and rats are inconsistent and that changes in alanine levels are closely related to its participation in multiple metabolic pathways, [37][38][39]43 including gluconeogenesis, bile acid synthesis, fatty acid synthesis, and amino acid metabolism.…”
Section: Metabolomic Characterization Of Dvtmentioning
confidence: 99%